Looking for commitment: Finnish Open Access journals, infrastructure and funding - Ilva, Jyrki (Septentrio Conference Series, 2017)
Watch the VIDEO here. Since 2015, the Federation of Finnish Learned Societies and the National Library of Finland have been working on a joint project (www.kotilava.fi), which aims to provide the 100+ Finnish scholarly journals with the support they need for moving to an Open Access publication model. In essence, the mission of the project is conservative. It aims to preserve the current infrastructure consisting of journals mostly run by scholarly societies. The journals are provided a shared publication platform (Journal.fi) that they can use for free, and there will also be a new source of funding for OA journals. However, although the journals are expected to follow certain standards including the use of peer-review, persistent identifiers and open licenses, they will retain their independence and they will be run by the researcher communities in each field as before. Some OA activists insist that journals are an old legacy mechanism which is no longer needed in scholarly communication. However, as far as the Finnish domestic journals are concerned, many of them actually do have a substantial audience as journals both within and beyond the academia. In many cases they are also an important incubator for new content, not just an anonymous publication channel for unsolicited articles. Although it might be possible to create a generic national platform which would provide tools sufficient for the evaluation and dissemination of articles, the current journal-based infrastructure seems to be supported and preferred by the researcher communities. Of course, this may change at some point, but at the moment it seems to be a better idea to work with the journals and try to enhance the current system by adopting new technologies and increasing the visibility and usability of the content. The project has been developing a consortium-based model in which the Finnish research organizations would provide funding for participating journals. Since the journals are not owned by commercial entities, the subscription costs paid by research libraries have been minimal. This means that extra money will be needed as it is not possible to simply flip the current subscription-based funding model. The negotiations with stakeholders are still underway, but there is some optimism that an agreement will be reached. Although the proposed model uses the number of articles as a basis for distributing the costs between organizations of different size and publication volume, it is not meant to be an APC model. Instead of being merely an exchange of money for specified services the idea is that the participating organizations will make a commitment to support the domestic OA journal infrastructure. Although the participating journals are allowed to introduce APCs for authors from organizations which are not part of the consortium, few of them are likely to do so. Some libraries have had concerns that this may lead to a free-rider problem (“why should we pay if others can get the same service for free?”), but we hope that the shared benefits provided by consortium-funded OA journals will outweigh these issues.